Study protocol for a randomized control trial investigating the effectiveness of a multifaceted mHealth approach on adherence to antihypertensive treatment among patients in Pakistan - Arshed, Muhammad; Mahmud, Aidalina Binti; Umer, Muhammad Farooq; Mashhadi, Fawad; Kawish, Ayesha Babar (Professional Medical Publications, 2025)
Background & Objectives: Poor medication adherence is an essential contributor to Pakistan’s high prevalence of uncontrolled hypertension. This study will be aimed to assess the efficacy of a one-of-a-kind developed intervention in improving medication adherence and treatment outcomes in hypertension patients. Methods: Twleve months duration long randomized controlled trial from January to December 2021 will be carried out at Shaikh Zayed Medical Complex (SZMC), Lahore. A total of 440 patients aged 18 years and older diagnosed with hypertension in the last month with non-adherence to antihypertensive therapy <80% of pills used in the last 30 days and have access to a smartphone will be randomized into either the intervention group (n=220) or the control group (n=220). For the intervention arm, a comprehensive intervention, the “Multi-Aid-Package,” consisting of seven items: written, voice, and graphics messages, animated video, educational material, and a 24/7 help service, has been designed. Standard care will be provided to the control group. The primary outcome will be improved adherence to antihypertensive medication, while the secondary outcome will be an alteration in systolic blood pressure (SBP). The analysis will be intention to treat. Conclusion: According to this study, if the multifunctional Multi-Aid-Package proves to be a useful mobile health tool for improving hypertension patients’ medication adherence, it will also significantly affect systolic blood pressure. In Pakistan and other comparable low-and middle-income countries LMICs, the Multi-Aid-Package ought to be taken into consideration as a means of enhancing adherence to medications among hypertension patients.